APPLICATION OF MODERN METHODS AND TECHNOLOGIES OF SOFTWARE MODELING IN THE TRAINING OF IT SPECIALISTS - KUNDOS, MAKSYM; SOLOVEІ LIUDMYLA; HRYSYUK, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Methodological approaches to software modeling are considered in the article. Proposed modeling methods and tools for software development for IT projects. The importance of understanding the basics of modeling and analytics for modern IT specialists is determined. The research is based on the analysis of modern methods and technologies, such as Model-Driven Development (MDD) and Unified Modeling Language (UML), which contribute to the effective creation and management of complex software systems. The focus is on the importance of visualizing requirements, optimizing design, and improving communication between team developers. In particular, it is emphasized that modeling helps to detect errors in the early stages, which significantly reduces the risks and costs associated with their correction in the later stages of software development. The study analyzes the impact of adaptive methodologies such as Agile and DevOps on modeling, noting its role in enabling flexibility and rapid response to changing requirements. The results of the study confirm that the mastery of modern approaches to modeling is a necessary component of the professional training of future IT specialists, which allows them to successfully adapt to the dynamic IT market. Modeling is one of the key stages of the software development process, which ensures the formalization of requirements, the structuring of system components, and the creation of a basis for further design and implementation. Modern modeling methods and technologies make it possible not only to increase the efficiency of the development process but also to ensure the flexibility of systems in response to dynamic changes in business requirements. The use of modern modeling methodology is an important stage in the educational process because it helps students not only understand the basics of design but also prepares them for the challenges of real projects in the field of information technologies.